Morphological and viscoelastic properties of the Achilles tendon in the forefoot, rearfoot strike runners, and non-runners in vivo - Zhang, Xini; Deng, Liqin; Xiao, Songlin; Fu, Weijie (Frontiers in Physiology, 2023)
The purpose of this study was to investigate the differences in the morphological and viscoelastic properties of the Achilles tendon (AT) among different groups (rearfoot strikers vs. forefoot strikers vs. non-runners). Thirty healthy men were recruited, including habitual forefoot strike runners (n = 10), rearfoot strike runners (n = 10) and individuals with no running habits (n = 10). The AT morphological properties (cross-sectional area and length) were captured by using an ultrasound device. The real-time ultrasound video of displacement changes at the medial head of the gastrocnemius and the AT junction during maximal voluntary isometric contraction and the plantarflexion moment of the ankle, were obtained simultaneously by connecting the ultrasound device and isokinetic dynamometer via an external synchronisation box. The results indicated that male runners habitually forefoot strike exhibited significantly lower AT hysteresis than male non-runners (P < 0.05). Furthermore, a greater peak AT force during maximal voluntary contraction was observed in forefoot strike male runners than in male individuals with no running habits (P < 0.05). However, foot strike patterns were not related to AT properties in recreational male runners (P > 0.05). The lower AT hysteresis in male FFS runners implied long-term forefoot strike patterns could enhance the male-specific AT’s ability to store and release elastic energy efficiently during running, resulting in a more effective stretch-shortening cycle. The greater peak AT force in male FFS runners indicated a stronger Achilles tendon.